Call Option Pricing When the Exercise Price is Uncertain, and the Valuation of Index Bonds - Fischer, Stanley (Journal of Finance, 1978)
One of the most attractive features of the recent work on option pricing, ably summarized by Cox and Ross [3] and Smith [8], is the applicability of the option pricing formula to the pricing of other assets.As Black and Scholes [1] point out, corporate stock in a firm which has also issued bonds, can be regarded as a call, with the exercise price being the payment made to the bondholders .